Organoleptic properties and neuroimaging response on the perception of edible gels - Jakub Berčík; Vladimír Vietoris; Melina Korčok; Adriana Rusková; Ján Durec; Katarína Neomániová (Heliyon)
The rapidly increasing number of elderly people in the world highlights the need for the development of innovative foods with modified textures that do not expose the elderly to the risks associated with food consumption (risk of aspiration, suffocation, and chocking). Providing specific food such as edible gel for the elderly population and the study of their properties is a challenge for the scientific community. There are some available gels in the supermarkets destined for the sports population, with specific texture and technological properties that could be used and extrapolated for senior people. To explore this potential, five types of sport commercial gels purchased from a local Slovak market were characterized in order to evaluate their technological properties and to know if these types of gels are suitable for the senior population. The energy gels were evaluated using acceptance testing, involving 75 seniors who evaluated important organoleptic attributes by a combination of hedonic and intensity scales. The same consumer panel then profiled the gels using the Temporal Dominance of Sensations (TDS) technique. The prevalence of food neophobia was measured with the Food Neophobia Scale (FNS) and also using neuroimaging and biometric methods. The results suggest that there are significant differences in the perception of edible gels, as confirmed by measurements via electroencephalography (EEG) and Facereading. We conclude by suggesting the potential of specific foods such as edible gels for the elderly population as our findings also confirm that the composition of these specific and sustainable foods may elicit different perceptions. This highlights the need to use biometric and neuroimaging methods in food research in order to create more optimal formulations for specific populations.